Effect of Service Quality and Price Perception on the Purchase Decision of EMKL Services at PT Ardana Sejahtera Abadi - Muhammad Didan; Umar Farouk; Saptianing (Politeknik Negeri Semarang, 2025)
This study focuses on analyzing the influence of service quality and price perception on the decision to purchase Sea Freight Forwarding (EMKL) services at PT Ardana Sejahtera Abadi in Semarang. Against the backdrop of increasing international trade activity and fierce competition in the logistics industry, a company's ability to provide quality services and set competitive prices has become an important factor influencing customer purchasing decisions. The research method used is quantitative with a survey approach, employing a saturated sampling technique on the entire population of PT Ardana Sejahtera Abadi customers, totaling 34 respondents. The data analysis methods used were validity, reliability, and classical assumption tests. The research data were analyzed using multiple linear regression through SPSS version 26. The results of this study indicate that service quality has a positive and significant influence on purchasing decisions with a multiple linear regression value of Y = 0.255 + 0.351 X1 + 0.555 X2. Service quality and price perception contribute 47,5% to purchasing decisions, while the remainder is influenced by factors outside the scope of this study. These findings confirm that EMKL companies need to maintain service quality, particularly reliability and responsiveness, and implement value-based pricing strategies to ensure that price perceptions remain positive.